Scientometrics analysis of research activity and collaboration patterns in Chagas cardiomyopathy. - Gregorio González-Alcaide; Alejandro Salinas; José M Ramos (Public Library of Science (PLoS), 2018)
Chagas cardiomyopathy is a serious and common complication of Chagas disease.Through bibliometric and Social Network Analysis, we examined patterns of research on Chagas cardiomyopathy, identifying the main countries, authors, research clusters, and topics addressed; and measuring the contribution of different countries.We found 1932 documents on Chagas cardiomyopathy in the MEDLINE database. The most common document type was 'journal article', accounting for 79.6% of the total (n = 1538), followed by 'review' (n = 217, 11.2%). The number of published records increased from 156 in 1980-1984 to 311 in 2010-2014. Only 2.5% were clinical trials. Brazil and the USA dominated the research, participating in 53.1% and 25.7%, respectively, of the documents. Other Latin American countries where Chagas is endemic contributed less, with Bolivia, where Chagas disease is most prevalent, producing only 1.8% of the papers. We observed a high rate of domestic collaboration (83.1% of the documents published in 2010-2016) and a lower but significant rate of international collaboration (32.5% in the same time period). Although clinical research dominated overall, the USA, Mexico and several countries in Europe produced a considerable body of basic research on animal models. We identified four main research clusters, focused on heart failure and dysfunction (physical symptoms, imaging techniques, treatment), and on myocarditis and parasitemia in animal models.Research on Chagas cardiomyopathy increased over the study period. There were more clinical than basic studies, though very few of the documents were clinical trials. Brazil and the USA are currently leading the research on this subject, while some highly endemic countries, such as Bolivia, have contributed very little. Different approaches could help to redress this imbalance: encouraging researchers to conduct more clinical trials, launching international collaborations to help endemic countries contribute more, and strengthening links between basic and clinical research.